Análise dos problemas ambientais decorrentes do uso de pilhas e baterias e desenvolvimento de uma rota processual para tratamento das baterias Ni-Cd - Peixoto, Maria Clebiana da Silva (2011)
Aiming to analyze the environmental problems caused by use of batteries, we examined the Brazilian legislation on the matter and investigate what actions taken by retailers and manufacturers to the end of life of these products. It was found that for the materialization of this legislation is urgently needed effective monitoring, as well as a campaign of collective awareness of the problem. It was found that the only existing collection structure, although weak, is directed to the batteries of mobile phones, for the other types used in various equipment, it was noted that there is a real collection structure. Aiming at establishing a possible route for treatment of Ni- Cd, was it characterization. Therefore, initially, some batteries were dismantled by hand for the separation of internal components and understanding of its construction. The constituents of these batteries were characterized by chemical analysis by fluorescence, atomic absorption, X-ray diffraction, scanning electron microscopy with analysis of micro-regions, sieve analysis, specific area of analysis and thermogravimetric analysis. Using the factorial modeling of the leaching process has been defined the optimal parameters for leaching of the electrodes of these batteries, as follows: 14.5 mL/g, 6.2 mol/L and 80.5 oC, resulting in 98% yield. Based on the determination of the parameres of extraction, it was possible to propose an initial scheme for the separation of the metals of interest concerning the Ni-Cd battery.